2013
DOI: 10.1063/1.4816723
|View full text |Cite
|
Sign up to set email alerts
|

Windowless ultrasound photoacoustic cell for in vivo mid-IR spectroscopy of human epidermis: Low interference by changes of air pressure, temperature, and humidity caused by skin contact opens the possibility for a non-invasive monitoring of glucose in the interstitial fluid

Abstract: The application of a novel open, windowless cell for the photoacoustic infrared spectroscopy of human skin is described. This windowless cavity is tuned for optimum performance in the ultrasound range between 50 and 60 kHz. In combination with an external cavity tunable quantum cascade laser emitting in the range from ~1000 cm(-1) to 1245 cm(-1), this approach leads to high signal-to-noise-ratio (SNR) for mid-infrared spectra of human skin. This opens the possibility to measure in situ the absorption spectrum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 30 publications
0
42
0
Order By: Relevance
“…The method demonstrated here can be used to increase the signal-to-noise ratio and lower the detection limit of samples regardless of whether the sample is in open or closed form in all phases; liquid, solid, and gas. Similar T-cells were reported earlier where the branch cavity controls the acoustic resonance [23,29]. We employed a combined approach of analytical and numerical simulations and experimental analysis.…”
Section: Discussionmentioning
confidence: 89%
“…The method demonstrated here can be used to increase the signal-to-noise ratio and lower the detection limit of samples regardless of whether the sample is in open or closed form in all phases; liquid, solid, and gas. Similar T-cells were reported earlier where the branch cavity controls the acoustic resonance [23,29]. We employed a combined approach of analytical and numerical simulations and experimental analysis.…”
Section: Discussionmentioning
confidence: 89%
“…In 2013, Pleitez et al (119,120) demonstrated an approach utilizing photoacoustic spectroscopy in the MIR regime for noninvasively monitoring glucose within the human epidermis, deploying an EC-QCL in combination with an open photoacoustic sampling cell (Figure 9). Data acquisition periods of approximately 5 s open up the possibility for continuous in vivo measurements, for example, aiming at future noninvasive diabetes control.…”
Section: Emerging Techniquesmentioning
confidence: 98%
“…During an oral glucose tolerance test, absorption signals were recorded from the skin of the forearm of a healthy volunteer with a photoacoustic setup [8]. Later, Pleitez et al introduced an ultrasound (50–60 kHz) windowless photoacoustic cell and a tunable QCL between 1000 cm −1 and 1245 cm −1 [9]. The use of a windowless cell minimized the influence of air pressure and temperature variations as well as the buildup of air humidity caused by the direct contact of a cell to the skin.…”
Section: Introductionmentioning
confidence: 99%